Growth of the mangrove crab Ucides cordatus (Brachyura, Ocypodidae) - Pinheiro, MAA; Fiscarelli, A. G.; Hattori, G. Y. (Crustacean Soc, 2005)
During monthly samplings between September 1998 and August 2000. 3,660 specimens of Ucides cordatus (Linnaeus, 1763) (2054 males and 1606 females) were obtained and examined for size (CW carapace width) to determine growth-age equations for each sex. This species showed a slower growth, with a marked seasonal oscillation, in females as compared to males, suggesting application of the seasonal and nonseasonal von Bertalanffy growth model, respectively. CW&PROP; and k constant were closely similar for the two sexes (CW&PROP; (male) = 90.3 mm: CW&PROP; (female) = 88.6 mm; k(male) = 0.28; k(female) = 0.26). The age at sexual maturity was estimated to be around 3 years, while the age at legal size (CW = 60 mm) was 3.8 and 4.7 years for males and females, respectively. In the laboratory, juvenile stages did not show differences in growth rates under the same temperature and photoperiod conditions.